2000
DOI: 10.1001/archsurg.135.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Chlorhexidine Lavage in the Treatment of Experimental Intra-abdominal Infection

Abstract: Hypothesis: Closed postoperative peritoneal lavage (CPPL) with chlorhexidine gluconate reduces the number of intraperitoneal bacteria and improves the outcome of intra-abdominal infection. Design: Laboratory animal trial. Interventions: Intra-abdominal infection was produced in mice by the cecal ligation and puncture technique. After 16 to 18 hours, the animals underwent relaparotomy and placement of an intra-abdominal catheter for CPPL. In the first experiment animals were randomly divided into 4 groups: no l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…Recently, van Westreenen et al [14] reported increased adhesion formation in a standard peritoneal ischaemia model in rats after peritoneal lavage with solutions as compared with a control group. However, peritoneal lavage facilitates the removal of pus, necrotic tissue or any other adjuvant substances from the peritoneal cavity in peritonitis and is a routine practice for many surgeons [3,5]. Saline solution is thought to be safe under these circumstances and is used as a standard lavage solution in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, van Westreenen et al [14] reported increased adhesion formation in a standard peritoneal ischaemia model in rats after peritoneal lavage with solutions as compared with a control group. However, peritoneal lavage facilitates the removal of pus, necrotic tissue or any other adjuvant substances from the peritoneal cavity in peritonitis and is a routine practice for many surgeons [3,5]. Saline solution is thought to be safe under these circumstances and is used as a standard lavage solution in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…The conglomerate of organs formed by dense adhesions was present in 60% of cases when gastric peritonitis was lavaged by chlorhexidine and in only Introduction Despite advancements in surgical and intensive care treatment, peritonitis still remains a life-threatening condition, with mortality as high as 30% [1]. The current treatment of peritonitis consists of (1) source control, (2) general resuscitation measures, (3) systemic antibiotic therapy and (4) mechanical reduction of bacterial inoculum [2][3][4][5]. Whether there is a need for peritoneal lavage in order to reduce bacterial counts and what solution is the best for this purpose is still a matter of debate.…”
mentioning
confidence: 99%
“…In these studies, the value of the lavage with physiological solution or antiseptics such as chlorexidine or povidone-iodine solution is unclear [13,16]. Indeed, some prospective randomized studies produced favorable conclusions [17], while others did not show any benefit [18]. In our study we expected an effect of the rifamycin peritoneal lavage on the outcome, the microbiology, and the adhesion score.…”
Section: Discussionmentioning
confidence: 73%
“…Chx-Glu has a low toxicity profile at therapeutic concentrations of 0.05% in animal models of peritonitis [34,35] and in the clinical setting [36]. Bondar et al [37] showed that the lavage with 0.05% Chx-Glu was effective and non-toxic in intraabdominal infection. 5-min application of 0.04% Chx-Glu was shown to be 100% effective min in vitro and in the treatment of the IPH [9].…”
Section: Histopathological Alterationsmentioning
confidence: 99%